2021
DOI: 10.3390/pathogens10020110
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy—A Story of Bacteria Interfering with the Host Cell Degradation Machinery

Abstract: Autophagy is a highly conserved and fundamental cellular process to maintain cellular homeostasis through recycling of defective organelles or proteins. In a response to intracellular pathogens, autophagy further acts as an innate immune response mechanism to eliminate pathogens. This review will discuss recent findings on autophagy as a reaction to intracellular pathogens, such as Salmonella typhimurium, Listeria monocytogenes, Mycobacterium tuberculosis, Staphylococcus aureus, and pathogenic Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 185 publications
0
30
0
Order By: Relevance
“…During the initiation of autophagy, Beclin 1 is part of the complex that plays a key role in phagophore nucleation [37]. Then, autophagosome formation is mediated by the ATG5-ATG12 conjugation system and the LC3 processing system [23]. E. coli facilitates pathogen colonization and growth by subverting autophagy in human colonic epithelial cells via downregulating ATG5 and LC3B-II protein levels [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the initiation of autophagy, Beclin 1 is part of the complex that plays a key role in phagophore nucleation [37]. Then, autophagosome formation is mediated by the ATG5-ATG12 conjugation system and the LC3 processing system [23]. E. coli facilitates pathogen colonization and growth by subverting autophagy in human colonic epithelial cells via downregulating ATG5 and LC3B-II protein levels [24].…”
Section: Discussionmentioning
confidence: 99%
“…During the process of autophagy, LC3B-I is converted to LC3B-II by phosphatidylethanolamine conjugation. Thus, tracking the change of LC3B-II is indicative of autophagic activity [23]. Western blot analysis showed that there was a significant decrease in protein levels of LC3B-II and Beclin 1 and a significant increase in p62 protein expression after EPEC challenged compared with the control group (p < 0.01) which indicated that autophagic flux was impaired [30] in EPEC-infected IPEC-J2 cells (Figure 3A).…”
Section: Eps Restored the Autophagy Flux Inhibited By Epec In Ipec-j2 Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, S. aureus has developed mechanisms to escape from the autophagy pathway (Riebisch et al, 2021). It has been demonstrated that S. aureus can block autophagosome maturation via phosphorylation of mitogen-activated protein kinase 14 (MAPK14) and ATG5 in murine fibroblasts (Neumann et al, 2016).…”
Section: Manipulation Of Autophagy On S Aureus In Non-professional Phagocytesmentioning
confidence: 99%
“…A plethora of studies has suggested the role of autophagy in innate immunity to protect cells against host infection by intracellular bacteria and viruses, a type of selective macroautophagy called xenophagy. Some pathogens have developed mechanisms to evade or control autophagy for their infection [82,[434][435][436][437][438][439][440][441][442][443]. Moreover, it has been shown that autophagy plays a role in adaptive immunity by increasing the presentation of antigens on major histocompatibility complex (MHC) class II molecules upon pathogenic infection, highlighting the role of autophagy in the T-cell-mediated immune response [444][445][446][447][448].…”
Section: Autophagy In Health and Diseasementioning
confidence: 99%